Membuat Email - Manopo N. K. V; Kalo A. P. O; Lumendek H. J; Rawung F. S; Malingkas C. A; Paputungan E; Mandagi R; Gobel N. A; Rember D. C; Saputri C. A; Tiwa J; Keyeh R. B; Tololiu S (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Email is a fairly cheap solution, can be accessed from anywhere, and rarely experiences delays in delivery, because in general (if there are no problems) emails can usually be sent within 2-5 minutes at most. The purpose of writing this paper is to find out how to create an email.